Self-Assembly, Tunable Hydrogel Properties, and Selective Anti-Cancer Activity of a Carnosine-Derived Lipidated Peptide - Castelletto, Valeria (ACS Appl Mater Interfaces, 2019)
[Image: see text] A novel lipopeptide C(16)KTTβAH was designed that incorporates the KTT tripeptide sequence from “Matrixyl” lipopeptides along with the bioactive βAH (β-alanine-histidine) carnosine dipeptide motif, attached to a C(16) hexadecyl lipid chain. We show that this peptide amphiphile self-assembles above a critical aggregation concentration into β-sheet nanotape structures in water, phosphate-buffered saline (PBS), and cell culture media. Nanotape bundle structures were imaged in PBS, the bundling resulting from nanotape associations because of charge screening in the buffer. In addition, hydrogelation was observed and the gel modulus was measured in different aqueous media conditions, revealing tunable hydrogel modulus depending on the concentration and nature of the aqueous phase. Stiff hydrogels were observed by direct dissolution in PBS, and it was also possible to prepare hydrogels with unprecedented high modulus from low-concentration solutions by injection of dilute aqueous solutions into PBS. These hydrogels have exceptional stiffness compared to previously reported β-sheet peptide-based materials. In addition, macroscopic soft threads which contain aligned nematic structures can be drawn from concentrated aqueous solutions of the lipopeptides. The anti-cancer activity of the lipopeptide was assessed using two model breast cancer cell lines compared to two fibroblast cell line controls. These studies revealed selective concentration-dependent cytotoxicity against MCF-7 cancer cells in the mM concentration range. It was shown that this occurs below the onset of lipopeptide aggregation (i.e., below the critical aggregation concentration), indicating that the cytotoxicity is not related to self-assembly but is an intrinsic property of C(16)KTTβAH. Finally, hydrogels of this lipopeptide demonstrated slow uptake and release of the Congo red dye, a model diagnostic compound.